Peningkatan Keterampilan Menulis Teks Biografi Tokoh Inspiratif dengan Model Project Based Learning Berbantuan Platfrom KBBI Daring di Kelas X AKL 1 SMKN 2 Semarang - Sari, Ratna; Asrofah,; Sri Wahyuni, (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This study aims to describe the implementation of the project based learning (PjBL) learning model by utilizing online KBBI in improving the skills of writing biographical texts of inspirational figures in class X AKL 1 students of SMKN 2 Semarang. The method used is classroom action research (PTK) with quantitative and qualitative approaches. The subjects of the study consisted of class X students of SMKN 2 Semarang, with a purposive sampling technique to select one sample class, namely X AKL 1, which is also the location for the implementation of PPL 2. Data collection was carried out through tests and observations. Qualitative data were analyzed using scoring guidelines based on assessment instruments, while quantitative data were processed with descriptive statistics to measure the improvement in the ability to write biographical texts. The results showed an increase in the average value from the pre-cycle (57.38 - quite good), the first cycle (80 - quite good), to the second cycle (95.76 - very good). Overall, there was an increase in the skills of writing biographical texts by 38.39%. Thus, it can be concluded that the PjBL model is effective in improving students' ability to write biographical texts.